Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.7 - Complex Numbers - Exercise Set: 37



Work Step by Step

We are given the expression $(\sqrt 3+2i)(\sqrt 3-2i)$. We can use the FOIL method to simplify. F=$\sqrt 3\times\sqrt 3=(\sqrt 3)^{2}=3$ O=$\sqrt 3\times-2i=-2i\sqrt 3$ I=$2i\times\sqrt 3=2i\sqrt 3$ L=$2i\times-2i=-4i^{2}=-4\times-1=4$ Now,we can combine these terms. $(3)+(-2i\sqrt 3)+(2i\sqrt 3)+(4)=7=7+0i$ We know that $i^{2}=-1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.